2022
DOI: 10.2147/idr.s391674
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Molecular Mechanism of Polymyxin B Resistance in Carbapenem-Resistant Klebsiella pneumoniae Isolates from a Tertiary Hospital in Fujian, China

Abstract: Background The emergence of polymyxin B resistance among carbapenem-resistant Klebsiella pneumoniae (CRKP) causes clinical treatment to be more difficult. We aimed to investigate the risk factors and resistance mechanisms in the polymyxin resistant CRKP (PR-CRKP) strains. Methods From January 2021 to January 2022, 239 CRKP strains were selected, all of which were analyzed using antimicrobial susceptibility testing and clinical data. Polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It was reported that coronary heart disease is an independent risk factor that predisposes patients to PR resistance. 28 Chronic renal failure has been shown as a risk factor in critically ill patients with PR and carbapenemase-producing Enterobacterales in a previous study, which also included other risk factors such as surgical procedures, indwelling devices (urinary catheters), and transfer between hospital wards. 16 Other risk factors associated with colistin resistance in Gram-negative bacilli include neurological disease, residence in a nursing facility prior to admission, receipt of carbapenems or an antimicrobial with anti-methicillin-resistant Staphylococcus aureus activity, and receipt of ventilatory support.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that coronary heart disease is an independent risk factor that predisposes patients to PR resistance. 28 Chronic renal failure has been shown as a risk factor in critically ill patients with PR and carbapenemase-producing Enterobacterales in a previous study, which also included other risk factors such as surgical procedures, indwelling devices (urinary catheters), and transfer between hospital wards. 16 Other risk factors associated with colistin resistance in Gram-negative bacilli include neurological disease, residence in a nursing facility prior to admission, receipt of carbapenems or an antimicrobial with anti-methicillin-resistant Staphylococcus aureus activity, and receipt of ventilatory support.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are several other genes potentially associated with the virulence of KP, including kpn gene involved in capsule polysaccharide synthesis, and wcaG and wagGI genes encoding extracellular toxins. Research has suggested that genes related to iron carriers, pili, and lipopolysaccharides are located on virulence plasmids in highly virulent KP strains and serving as specific molecular markers for high-virulent strains (Russo et al 2019; Xu Shuibao et al 2017). Therefore, it can be inferred that wabG, uge, and ycf may potentially serve as high virulence genes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are several other genes potentially associated with the virulence of KP, including kpn gene involved in capsule polysaccharide synthesis, and wcaG and wagGI genes encoding extracellular toxins. Research has suggested that genes related to iron carriers, pili, and lipopolysaccharides are located on virulence plasmids in highly virulent KP strains and serving as speci c molecular markers for high-virulent strains [36,37]. Therefore, it can be inferred that wabG, uge, and ycf may potentially serve as high virulence genes.…”
Section: Discussionmentioning
confidence: 99%